2020
DOI: 10.4103/jcd.jcd_43_20
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of smear layer removal by using ethylenediamine tetraacetic acid, citric acid, and maleic acid as root canal irrigants: An in vitro scanning electron microscopic study

Abstract: Introduction: Irrigants remove or dissolve smear layer formed during instrumentation. Thus it is important to study the effect of different irrigant solutions on smear layer removal. Objectives: The aim of this study is to determine which irrigant effectively removes the smear layer from the coronal, middle, and apical third of the root canal. Materials and Methodology: One hundred and twenty single-rooted mandibular premolars were decoronate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Results of the current study demonstrated that the removal of the smear layer was statistically less effective in the apical third of the root canal compared to coronal and middle thirds, regardless of the irrigation solution used except for saline solution. This is in agreement with previous results and could be explained by less diameter of apical third, decreased permeability and presence of sclerosed dentin in the apical third which limits the chelating effect of any chelator (46) . The result of Pearson correlation test revealed that there was a positive correlation between the results of antibacterial action and smear layer removal ability of the tested irrigants and this correlation was statistically significant (P > 0.05(.…”
Section: Natural Vinegars As Endodontic Irrigantssupporting
confidence: 93%
“…Results of the current study demonstrated that the removal of the smear layer was statistically less effective in the apical third of the root canal compared to coronal and middle thirds, regardless of the irrigation solution used except for saline solution. This is in agreement with previous results and could be explained by less diameter of apical third, decreased permeability and presence of sclerosed dentin in the apical third which limits the chelating effect of any chelator (46) . The result of Pearson correlation test revealed that there was a positive correlation between the results of antibacterial action and smear layer removal ability of the tested irrigants and this correlation was statistically significant (P > 0.05(.…”
Section: Natural Vinegars As Endodontic Irrigantssupporting
confidence: 93%
“…The use of different solutions has been implemented to improve dentin conditioning and an effective remove of the SSL throughout the space created for the fiber post; these solutions include acid solutions, that is, ethylenediaminetetraacetic acid (EDTA) [10,25,34], OA [25,30,34], maleic acid [20], and citric acid at several concentrations such as 10%, 20%, and 50% [9,25]. Also, the use of several combined solutions allows a reduction of superficial tension, facilitating irrigants contact with dentinal walls, and enhancing SSL removal [35]; some examples are MTAD [34,36,37] and Q-mix [18,24]. There activity is summarized in Table 1.…”
Section: Conditioning Solutionsmentioning
confidence: 99%
“…Remove the SL and open the dentinal tubules [40] Citric acid Demineralizing solution [18] Maleic acid Demineralization of the intertubular dentin [18,41] Table 1. Cont.…”
Section: Orthophosphoric Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Maleic acid is a mild organic acid that removes the smear layer effectively at concentrations of 5% and 7%. [ 6 ] MTAD is a new irrigating solution containing a mixture of a tetracycline isomer, an acid, and a detergent developed by Torabinejad et al .…”
Section: Introductionmentioning
confidence: 99%